1996
DOI: 10.1523/jneurosci.16-16-04872.1996
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in GABAAReceptor Subunit mRNA Expression by Hypothalamic Magnocellular Neurons in the Adult Rat

Abstract: The magnocellular hypothalamic neurons exhibit a substantial degree of structural and functional plasticity over the time of pregnancy, parturition, and lactation. This study has used in situ hybridization techniques to examine whether the content of ␣ 1 , ␣ 2 , ␤ 2 , and ␥ 2 GABA A receptor subunit mRNAs expressed by these cells fluctuates over this period. A process of regional, followed by cellular and then topographical, analyses within the supraoptic (SON) and posterior paraventricular (PVN) nuclei reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 46 publications
7
58
1
Order By: Relevance
“…Late pregnancy was also associated with an increase in the abundance of the ␣ 1 subunit mRNA in oxytocin neurons of the supraoptic nucleus of the hypothalamus (Fénelon and Herbison, 1996). Our present immunohistochemical data confirm our previous observation of the downregulation of ␥ 2 subunit expression in the hippocampus of rats during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Late pregnancy was also associated with an increase in the abundance of the ␣ 1 subunit mRNA in oxytocin neurons of the supraoptic nucleus of the hypothalamus (Fénelon and Herbison, 1996). Our present immunohistochemical data confirm our previous observation of the downregulation of ␥ 2 subunit expression in the hippocampus of rats during pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings do not necessarily demonstrate that direct phosphorylation of GABA A receptors by PKC is prevented; however, several phosphorylation sites are present at the ␥2 and the ␤2 subunit (12, 13), both of which are expressed in the SON (see ref. 14). Furthermore activation of PKC has variable effects on GABA A receptor activity (15)(16)(17)(18), which are likely to be caused by cell-specific differentiation in GABA A receptor subunit composition.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of different GABA A receptor subunits varies between brain regions and even cell types within a region (133) and can be differentially regulated by numerous factors, including neuronal activity (174), and the ovarian hormones estrogen (39,172) and progesterone (60,136,140,172,174). It was previously reported that GABA A receptors with a higher proportion of ␣ 1 -compared with ␣ 2 -receptor subunits were most sensitive to neurosteroid modulation (153), and expression of the ␣ 1 -subunit is increased in hypothalamic oxytocin neurons in late pregnancy (31,59). In the RVLM, expression of the ␣ 1 -subunit is several hundred times greater than expression of the ␣ 2 -subunit, suggesting that GABA A receptors in this region should be sensitive to neuro- Fig.…”
Section: Neurosteroid Metabolite Of Progesterone: a Contributor To Atmentioning
confidence: 99%